Singularity, violence and universality in Derrida’s ethics: Deconstruction’s struggle with decisionism - Stocker Barry (Filozofija i Društvo)
The starting point of the paper is Derrida’s early discussion of Lévinas, focusing on the suggestion that violence is paradoxically magnified in Lévinas’s attempt to articulate ethics as first philosophy within a metaphysics ostensibly free of violence. The next step is an examination of Derrida’s thoughts on Lévi-Strauss and Rousseau in Of Grammatology. Derrida’s comments on names and violence in Lévi-Strauss establish that ethics emerges through a distinction between the “good” interior and the “bad” exterior. Derrida’s subsequent remarks on Rousseau bring up his view of pity as a pre-social morality and the emergence of a social world that enacts violence upon the fullness of nature and the spontaneity of pity within a system of organized, competitive egotism. In his engagement with Celan, Derrida explores a poetics that conveys the sense of a particular, singular self as essential to ethics-defining itself in its separation yet inevitably caught up in universality. This theme develops into an examination of mass slaughter around the Hebrew Bible story of the “shibboleth”, highlighting the violent consequences of exclusionary conceptions of identity. In The Gift of Death, Derrida discusses the relationship between Paganism, Platonism, and Christianity through Patočka’s perspective, then returns to Judaism via Kierkegaard’s discussion of Abraham and Isaac. Derrida’s reflections on secrecy, the sacred, ethical paradox, the violence of ethical absolutism, and the aporetic nature of ethical decisions converge around a discussion of political decisionism in Schmitt and the broader ethical significance of decisionism, as it also appears in Benjamin.